2022
DOI: 10.1164/rccm.202201-0214oc
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Lung Hyperinflation Improves Cardiac Preload, Contractility, and Output in Emphysema: A Clinical Trial in Patients Who Received Endobronchial Valves

Abstract: Rationale: Pulmonary hyperinflation in patients with chronic obstructive pulmonary disease has been related to smaller cardiac chamber sizes and impaired cardiac function. Currently, bronchoscopic lung volume reduction (BLVR) with endobronchial valves is a treatment option to reduce pulmonary hyperinflation in patients with severe emphysema. Conclusions:We found that reduction of hyperinflation using BLVR with endobronchial valves significantly improved cardiac preload, myocardial contractility, and cardiac ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Another study that evaluated cardiac hemodynamics pre and post-EBV placement in 24 patients showed significant improvements in right ventricle end-diastolic volume index, cardiac output, stroke volume, ejection fraction, and strain measurements. Conversely, there was no change noted in pulmonary artery pressures [32]. This study stresses the multifaceted physiology of dyspnea in patients with emphysema and calls for additional studies that assess pulmonary mechanics and hemodynamics postlung volume reduction and the presence of PH should not be considered as an absolute contra-indication.…”
Section: Patient Selectionmentioning
confidence: 65%
“…Another study that evaluated cardiac hemodynamics pre and post-EBV placement in 24 patients showed significant improvements in right ventricle end-diastolic volume index, cardiac output, stroke volume, ejection fraction, and strain measurements. Conversely, there was no change noted in pulmonary artery pressures [32]. This study stresses the multifaceted physiology of dyspnea in patients with emphysema and calls for additional studies that assess pulmonary mechanics and hemodynamics postlung volume reduction and the presence of PH should not be considered as an absolute contra-indication.…”
Section: Patient Selectionmentioning
confidence: 65%
“…Hyperinflated lungs of severe emphysematous patients have shown to be associated with intrathoracic hypovolemia and decreased biventricular preload and reduced cardiac performance 35 . In a recent study 36▪▪ , in a cohort of 28 patients eligible for BLVR, MRI scans of the heart were performed before and after BLVR and revealed a significant and clinically relevant improvement of the right ventricular diastolic filling (primary outcome) and stroke volume, and even left ventricular stroke volume and ejection fraction, illustrating that BLVR is able to reverse the negative impacts of lung hyperinflation on the heart.…”
Section: Extrapulmonary Effects Of Lung Volume Reductionmentioning
confidence: 99%
“…An Australian study showed that twice weekly sessions for 8 weeks of telerehabilitation was broadly equivalent to face to face sessions in terms of exercise improvement but possibly inferior in improving breathlessness 59 . Meantime our understanding of endoscopic lung volume reduction (EVLR) grows with Swedish workers showing that cardiac preload, myocardial contractility and cardiac output all improved when pulmonary hyperinflation was decreased 60 . EVLR is less effective when collateral ventilation is present between lobes but Ing et al abolished this problem with endoscopic polymer foam placement before valve insertion leading to results comparable to patients with complete fissures between the lobes 61 thereby increasing the number of treatable patients.…”
Section: Prevention and Treatmentmentioning
confidence: 99%